PENGARUH IMPLEMENTASI KEBIJAKAN TERHADAP KUALITAS PELAYANAN BANDUNG INTEGRATED MANPOWER MANAGEMENT APPLICATION - Tamara, Cindi; Suhara, Ero (Ilmu Pemerintahan Universitas Langlangbuana, 2023)
The problem in this research is the low quality of service in the Employment Application, namely the Bandung Integrated Manpower Management Application (BIMMA) which is implemented by the Bandung City Employment Service. According to the researcher's assumption, the low quality of service in this application is still influenced by the Policy Implementation variable. Based on these problems, the problem formulation proposed is: